Waistcoats & weaponry - Carriger, Gail (Carriger, Gail. Finishing school, 2014)
In her alternate England of 1851, while taking her friend Sidheag by train to her werewolf pack in Scotland, sixteen-year-old Sophronia uncovers a plot that threatens to dissolve all of London into chaos and must decide where her loyalties lie once and for all.